The Impact of Customer Satisfaction on Loyalty in Jordanian Banks: The Mediating Role of Corporate Reputation - Alhawamdeh, Ahmad Kamal; Alfukaha, Feras Ahmad; Padlee, Siti Falindah; Salleh, Ahmad Munir Mohd; Saadon, Mohd Saiful Izwaan (International Journal of Management and Sustainability, 2022)
Customer satisfaction is a critical factor in improving bank performance and increasing revenue. Banks must continue to strengthen their relationships with customers because the banking system is highly responsive to customer choices. Customers are inundated with offers and services, particularly online, creating dissatisfaction with the status quo. The purpose of this research is to examine the mediating effect of corporate reputation on the relationship between customer satisfaction and loyalty in Jordanian commercial banks. A quantitative research design is used to achieve the research objectives. The data are gathered from the customers of Jordanian commercial banks in Amman. 350 valid questionnaires are used in the analysis. The findings of the study reveal that corporate reputation mediates the relationship between customer satisfaction and loyalty among bank customers. Therefore, the study recommends that banks make better use of their corporate reputation in their strategies, for instance in social initiatives and marketing programs, to ensure effective and sustainable engagement, which will improve the bank’s position in the minds of customers.